1985
DOI: 10.1182/blood.v66.2.358.358
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic significance of Sezary cells in peripheral blood smears from patients with cutaneous T cell lymphoma

Abstract: Blood smears stained with Wright-Giemsa were obtained from 124 patients with pathologically confirmed cutaneous T cell lymphoma (CTCL), 70 patients with various other cutaneous disorders, and ten healthy adult volunteers. These were examined in a blinded fashion for atypical lymphocytes with cerebriform nuclei (CLs), which were characterized further according to cell diameter. CLs, comprising up to 15% of lymphocytes in smears, were observed in 20% of the patients with benign dermatitis. CLs, comprising up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Moreover, Bernengo et al 2 found no correlation between the overall level of Sézary cells and survival, but determined that large circulating Sézary cells (exceeding 15 lm in diameter) constituted a prognostic factor (P < 0AE001). Schechter et al 16 and Vonderheid et al 17 had previously reported similar findings for large Sézary cells, which are much more specific and easily identifiable than small ones that can be confused with circulating lymphocytes.…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, Bernengo et al 2 found no correlation between the overall level of Sézary cells and survival, but determined that large circulating Sézary cells (exceeding 15 lm in diameter) constituted a prognostic factor (P < 0AE001). Schechter et al 16 and Vonderheid et al 17 had previously reported similar findings for large Sézary cells, which are much more specific and easily identifiable than small ones that can be confused with circulating lymphocytes.…”
Section: Discussionmentioning
confidence: 56%
“…In MF no DRB were detected with Immunoglobulin heavy and light chain gene probes. In two patients with Sezary syndrome (7,9) analysis of peripheral blood DNA revealed a rearrangement of the Ig heavy chain but germ line K and X light chains (Fig. 5).…”
Section: Genotypementioning
confidence: 98%
“…YCOSIS FUNGOIDES (MF) and Sezary syndrome are M distinct clinicopathologic entities which form part of the spectrum of cutaneous T-cell lymphomas (CTCL). ' MF is a primary cutaneous lymphoma whereas Sezary syndrome is characterized by a pruritic infiltrated erythroderma, lymphadenopathy, and the presence of atypical No. 7 TCR GENE ANALYSIS IN CTCL Whittaker et al 1573 implications.…”
mentioning
confidence: 99%
“…The presence of large Sézary cells (> 14 µm) is seen only with malignant disease, so a diagnosis of E‐CTCL can be made with certainty 26 . For the small and medium‐sized variants, additional data are required to distinguish neoplastic from reactive lymphocytes.…”
Section: Blood Involvement (Central Column)mentioning
confidence: 99%